Oncogenes inhibition with the use of antisense oligonucleotides as a new method of cancer treatment - Nurzyńska, Daria (Contemporary Oncology/Współczesna Onkologia, 2003)
Neoplastic transformation of the cell is the result of the protooncogene mutation resulting in the formation of an oncogene whose expression results in increased or deregulated production or malfunction of proteins regulating cell growth, proliferation and maturation. Elucidation of important facts concerning the human genome, and in particular an oncogene nucleotide sequence has opened new possibilities of interception of protein synthesis due to the fact, that their aminoacid sequence is determined by the sequence of nucleotides, comprising DNA and mRNA. It is known, that as long as coding DNA strand (sens strand) is combined with its complementary strand (i.e. antisense strand) then independently of the (normal or mutated) sequence it cannot be transcribed to mRNA. Therefore, the antisense strand blocks the sens strand. This phenomenon forms the background for the attempts of the therapeutic use of antisense oligonucleotides for blocking both DNA and mRNA. Additionally, chemical modification of such oligonucleotides increased their resistance to intracellular degrading enzymes while encapsulation in liposomes allowed for better penetration into cells. Utilisation of antisense oligonucleotides binding specifically to selected mRNAs blocks gene expression and prevents the synthesis of the protein coded by that gene. Thus, antisense oligonucleotides blocking the oncogene message can neutralize consequences of the existence of this oncogene. The activity of antisense oligonucleotides agains several human oncogenes is currently under study. This article reviews known mechanisms of action and expectations associated with the inhibition of just a few of them: bcl-2, ras, raf and protein kinase C gene.